THE PURITANISM OF THE PROGRESSIVE TRADITIONALISM: Dynamics of Religious Life in Madura in Perspective on Conflict Theory of Lewis Coser - Edi Susanto (IAIN Ponorogo, 2018)
Abstract: This article is based on the phenomenological qualitative sociological research seeks to describe the research focus; the first, the spread of Islamic Puritanism ideology in an area of Progressive Traditionalism, especially on Madura island, second, the contact between Islamic Puritanism ideology and the ideology of Progressive traditionalism, and third, the implications of the contact between Islamic Puritanism ideology and ideology of Progressive Traditionalism especially in Madura. From the study, it was concluded that Islamic Puritanism ideology spread across the basis area of Progressive Traditionalism in Madura through traditional means (direct contact) and through media and modern preaching, while patterns of intersection between Islamic Puritanism Ideology and the ideology of Traditionalism Progressive in Madura involves a pattern of conflict and peaceful means, even though it is actually artificial peace like fire in the husk, and the implications of the contact between Islamic Puritanism and Progressive Traditionalism ideology to a certain extent is able to realize the reorientation of the religious pattern of progressive traditionalists and Islamic Puritans by being able to reduce the relative deprivation mentality and the attitude of alienation also the most authentic feeling.الملخص: هذا البحث العلمي يجري على أساس المنهج النوعي الاجتماعي الظواهري ويحاول إلى وصف تركيز البحث كما يلي؛ أولا: انتشار الفكر البيوريتاني الإسلامي في وسط مجتمع التقاليد التقدمي الإسلامي خاصة في جزيرة مادورا، ثانيا: نمط الاتصال بين الفكر البيوريتاني الإسلامي وبين عقيدة مجتمع التقاليد التقدمي الإسلامي، وثالثا: آثار الاتصال بين فكر البيوريتاني الإسلامي وبين فكر مجتمع التقاليد التقدمي الإسلامي. ودلت نتيجة هذا البحث على الأمور الآتية؛ وهي انتشار الفكر البيوريتاني الإسلامي في وسط مجتمع التقاليد التقدمي الإسلامي في جزيرة مادورا عن طريق الاتصال الاجتماعي المباشر واستخدام وسائل الإعلام والدعوة المعاصرة. ونمط الاتصال بين الفكر البيوريتاني الإسلامي وبين فكر مجتمع التقاليد التقدمي الإسلامي في مادورا يجري عن طريق الصراع والسلام. ولكن السلام مزيّف مصطنع مثل النار داخل الحظب. وتداعيات الاتصال بين مجتمع البيوريتاني الإسلامي ومجتمع التقاليد التقدمي الإسلامي إلى حد ما يستطيع أن يحقق إعادة التوجيه الديني حول مجتمع التقليديين التقدميين الإسلاميين والبيوريتانيين الإسلاميين من خلال القدرة على الحد من عقلية الحرمان النسبي وموقف الاغتراب و شعور الأصالة.Abstrak: Artikel ini berbasis pada penelitian kualitatif sosiologis fenomenologis berusaha mendeskripsikan fokus penelitian; pertama, penyebaran ideologi Puritanisme Islam di daerah kantong Tradisionalisme Progresif khususnya di pulau Madura, kedua, pola persentuhan ideologi Puritanisme Islam dengan ideologi kalangan radisionalisme Progresif dan ketiga, implikasi persentuhan ideologi Puritanisme Islam dengan ideologi kalangan Tradisionalisme Progresif khususnya di Madura. Dari studi tersebut diperoleh kesimpulan bahwa penyebaran Ideologi Puritanisme Islam di daerah kantong Tradisionalisme Progresif di Madura ditempuh melalui cara-cara tradisional (kontak langsung) dan melalui media dan dakwah modern. Pola persentuhan Ideologi Puritanisme Islam dengan ideologi kalangan Tradisionalisme Progresif di Madura melalui pola konflik dan dengan cara damai, meskipun damai semu seperti api dalam sekam, dan implikasi persentuhan Ideologi Puritanisme Islam dengan Ideologi kalangan Tradisionalisme Progresif hingga tahapan tertentu mampu mewujudkan reorientasi pola keberagamaan kalangan tradisionalis progresif maupun kalangan Puritanis Islam dengan syarat mampu mengurangi mental deprivasi relatif dan sikap keterasingan dan perasaan paling otentik.